2011
DOI: 10.1016/j.fertnstert.2011.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Are there subtle genome-wide epigenetic alterations in normal offspring conceived by assisted reproductive technologies?

Abstract: Objective To review recent data regarding subtle, but widespread epigenetic alterations in phenotypically normal offspring conceived of ART compared to offspring conceived in vivo. Design A PubMed computer search was performed to identify relevant articles. Setting Research institution. Intervention(s) None. Result(s) Studies in animals indicate that in vitro culture may be associated with widespread alterations in imprinted genes, compared to in vivo-conceived offspring. Recently, studies in humans ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 58 publications
(113 reference statements)
1
21
0
2
Order By: Relevance
“…In total, the studies comparing DNA methylation between children conceived in vitro and children conceived in vivo point to subtle differences at many genes. In agreement with data derived from experiments in the mouse, extraembryonic tis- Modified from data in Batcheller et al (2011).…”
Section: Moving From Biomarkers To Physiology and From Associations Tsupporting
confidence: 84%
See 1 more Smart Citation
“…In total, the studies comparing DNA methylation between children conceived in vitro and children conceived in vivo point to subtle differences at many genes. In agreement with data derived from experiments in the mouse, extraembryonic tis- Modified from data in Batcheller et al (2011).…”
Section: Moving From Biomarkers To Physiology and From Associations Tsupporting
confidence: 84%
“…Such comparisons have been performed in multiple laboratories, initially targeting small numbers of imprinted genes (reviewed by Batcheller et al 2011; systematic review and meta-analysis by Lazaraviciute et al 2014;Nelissen et al 2014;Whitelaw et al 2014;Melamed et al 2015), under the assumption that imprinted genes might be more susceptible to effects of epigenetic disruption (Table 2), and in a modest numbers of patients.…”
Section: Assisted Reproductive Technologies (Art)mentioning
confidence: 99%
“…ART procedures are associated with epigenetic modifications of genes related to growth and metabolism(28,29) as well as not achieving catch-up body weight in infancy. (12) Perhaps feeding practices are altered to compensate for the unique health and growth of infants conceived with these technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is also a small but significant increase in imprinting disorders, including Angelman and Beckwith-Wiedemann syndromes [10]. While some studies of children conceived by ART showed no clear metabolic abnormalities [11,12], others have shown statistically significant differences in fat deposition, increased blood pressure, and increased fasting glucose [13][14][15].…”
Section: Introductionmentioning
confidence: 99%